Functionalization of the Village Head as Customary Leader in the Social Field in South Sumatra - Abdullah, Abdullah; Hasan, KN. Sofyan; Rumesten, Iza; Pasyah, Taroman (Brawijaya Law Journal, 2020)
The presence of the New Order government has brought about changes in the lowest level of government, which fairly basic leads to some institutional unification and uniformity. This has resulted in the loss of legal community units in Indonesia. The loss of indigenous community units began with the beginning of Law Number 5 of 1979 on Village Governance as a follow-up to the birth of Law Number 5 of 1974 on the Principles of Government in the Regions. Correspondingly, in South Sumatra, the lowest institutional governance tool, which is also a territorial indigenous community unit called Marga was abolished through the Decree of the Governor of South Sumatra No.142/ KPTS/1983. With the abolition of the Marga, it implies the loss of a typical indigenous institution of South Sumatra, which was merged into the Village institution as stipulated in Law Number 5 of 1979 on Villages. As a result, all the lowest institutions in South Sumatra switched their names to villages including, their functions and authorities. The removal of the Marga government and being replaced with the Village, has resulted in the loss of social functions and the function of resolving disputes customarily manner in the community. The function shift of the village head was not necessarily the transfer of the authority of the pesirah Margahead to the village head in resolving arising problems in the community. As a result of this obscurity of the function, all arising problems in the community should resolve by the formal public law determined by the state. This results in an imbalance in the lowest community, including in villages in South Sumatra, to break the chain, the research framework has carried out to answer these problems.